Long-Term Effects of Aluminium Dust Inhalation - Peters, S.; Reid, Alison; Fritschi, Lin; de Klerk, N.; Musk, A. (BMJ Group, 2013)
Objectives During the 1950s and 1960s, aluminium dust inhalation was used as a potential prophylaxisagainst silicosis in underground miners, including in Australia. We investigated the association betweenaluminium dust inhalation and cardiovascular, cerebrovascular and Alzheimer’s diseases in a cohort ofAustralian male underground gold miners. We additionally looked at pneumoconiosis mortality toestimate the effect of the aluminium therapy. Methods SMRs and 95% CI were calculated to compare mortality of the cohort members with that ofthe Western Australian male population (1961–2009). Internal comparisons on duration of aluminium dust inhalation were examined using Cox regression.Results Aluminium dust inhalation was reported for 647 out of 1894 underground gold miners. During42 780 person-years of follow-up, 1577 deaths were observed. An indication of increased mortality ofAlzheimer’s disease among miners ever exposed to aluminium dust was found (SMR=1.38), although it was not statistically significant (95% CI 0.69 to 2.75). Rates for cardiovascular and cerebrovascular death were above population levels, but were similar for subjects with or without a history of aluminium dust inhalation. HRs suggested an increasing risk of cardiovascular diseasewith duration of aluminium dust inhalation (HR=1.02, 95% CI 1.00 to 1.04, per year of exposure). Nodifference in the association between duration of work underground and pneumoconiosis was observedbetween the groups with or without aluminium dust exposure.Conclusions No protective effect against silicosis was observed from aluminium dust inhalation. Conversely, exposure to aluminium dust may possibly increase the risk of cardiovascular disease and dementia of the Alzheimer’s type.